Integrating knowledge management in sustainability risk management practices for company survival - Abdul Manab, Norlida; Abdul Aziz, Nazliatul Aniza (Growing Science Ltd., 2019)
Sustainability risk management (SRM) is an approach that manages the broad spectrum of risks arising from sustainability issues such as climate change, resource depletion and natural catastrophes. SRM is an extension to Enterprise Risk Management (ERM) that aims to maximize environmental, social and economic performances for a company’s survival.In an SRM practice, knowledge management is a strategic resource for companies to sustain in the rapidly-evolved business environment. It provides a solution to address the unknown risks associated with environmental complexity. Thus, the aim of this study is to examine the moderating effect of knowledge management on the relationship between SRM critical factors (ERM bases and organizational resilience) and company survival among public listed companies (PLCs) in Malaysia. Partial Least Squares Structural Equation Modelling (PLS-SEM) technique is used to analyze the hypothetical model which is developed in this study.The result shows that knowledge management moderates the relationship between organizational resilience and company survival. This finding signifies that knowledge management is an important strategic resource to assist companies to develop effective risk management strategy. This will lead to better decision-making and risk controls which influence stakeholder value and company reputation. The study also finds that ERM bases and organizational resilience were significant towards company survival. Companies with strong ERM bases such as procedures, infrastructure and methods have higher chances of successful SRM implementation. Organizational resilience refers to the ability of a company to manage crises and disaster risks, which is crucial for a company’s survival. This study has both theoretical and practical implications. The result of this study provides relevant insights on the value of knowledge management to meet stakeholder expectations. It also provides a better understanding of the relationship between SRM implementation, its critical factors and company survival.